Gao Xingjian’s Dialogue with Literary and Visual Traditions - Łabędzka, Izabella (Porównania, 2020)
The paper is devoted to the contemporary Chinese prose and drama writer, painter, stage director and author of experimental art films, Gao Xingjian. My aim is to present his innovative solutions in the field of different arts and media. I try to analyze his works in a broad context of Eastern and Western culture and to show the flexibility with which he crosses the narrow borders of arts, makes use of the rich heritage of his native traditional culture, Chinese Taoist philosophy with its processual understanding of reality. I also point at his interest in the aesthetics of emptiness and artistic minimalism.